2013
DOI: 10.1002/jat.2965
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed proteins related to organophosphorus‐induced delayed neuropathy in the brains of hens

Abstract: Some organophosphorus compounds can cause organophosphate-induced delayed neuropathy (OPIDN). Incidents have been documented for decades, however, little is known about which proteins contribute to the initiation, progression and development of OPIDN. In this study, 51 hens were divided into three groups. The tri-ortho-cresyl-phosphate (TOCP) group was treated with 1000 mg kg(-1) TOCP whereas the control group was treated with an equivalent volume of vehicle. The PMSF + TOCP group was treated subcutaneously wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…TOCP has been shown to bind to neuropathy target esterase (NTE) and leads to aging reaction of NTE, thereby inhibits its enzymatic activity, which is associated with the initiation, progression and development of OPIDN [35]. Jiang et al [2] reported that the down-regulated expression of glutamine synthetase (GS) might be associated with the delayed neuropathy induced by TOCP through the disruption of homeostasis of the glutamate (Glu)-glutamine (Gln) cycle and cytosolic calcium concentration. Zou et al [32] found that the delayed neuropathy induced by TOCP might be mediated by the activation of mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TOCP has been shown to bind to neuropathy target esterase (NTE) and leads to aging reaction of NTE, thereby inhibits its enzymatic activity, which is associated with the initiation, progression and development of OPIDN [35]. Jiang et al [2] reported that the down-regulated expression of glutamine synthetase (GS) might be associated with the delayed neuropathy induced by TOCP through the disruption of homeostasis of the glutamate (Glu)-glutamine (Gln) cycle and cytosolic calcium concentration. Zou et al [32] found that the delayed neuropathy induced by TOCP might be mediated by the activation of mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…So adult hens are usually used as the animal model of OPIDN. Numerous studies show that the animal models of OPIDN have been successfully established in hens [2,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study used hens treated with chlorpyrifos (CPF) and demonstrated signs of delayed neurotoxicity including NTE inhibition, CI inhibition and decreased ATP levels. Also, Jiang et al (2014) demonstrated that disruption of glutamate-glutamine homeostasis in hens treated with TOCP might also contribute to OPIDN. Finally, a study in China by Zou et al (2012) concludes that TOCP exposure causes changes in the autophagy-related proteins Atg1, Atg5, and Becln1 and these changes may contribute to OPIDN.…”
Section: Mechanisms Of Opidnmentioning
confidence: 99%
“…86 Other intoxications are common in fowl, such as coccidiostats in waterfowl (found in chicken-formulated commercial diets) or pesticides (dimetridazole and organophosphorus pesticides). 87,88…”
Section: Neurologic Diseasementioning
confidence: 99%